Leading Change Through Service - McKay, Jim; Hamilton, Eric W. (Journal of Leadership, Accountability and Ethics, 2020)
Leaders are acutely aware that enduring and impactful organizational change is difficult to accomplish and even more difficult to sustain. Service to other educators is a powerful approach to naturally promote professional reflection and intentional change. Community High School District 117 developed a service program, Relief Through Leadership (RTL), to assist communities, schools, and teachers in Puerto Rico impacted by poverty, recent natural disasters, hurricanes, and earthquakes. Supported by the Board of Education, a group of dedicated educators raised money through individual, civic, and corporate sponsors to provide refurbished technology and professional development in instructional strategies to teachers. Teams of teachers skilled in instructional strategies and technology integration into the classroom delivered three days of professional development to their colleagues in Puerto Rico. Through impactful service and reflection, teachers’ personal and professional self-worth is bolstered likely improving the retention of skillful teachers. An increase in student engagement has been observed with participating teachers along with the intrinsic value of assisting teachers in Puerto Rico.